Study of The Effects of Carboxymethyl Chitosan on The Non-specific Defense System in The Carp (Cyprinus Carpio) - Ristyana Dewi Hernawati; Triyanto .; Murwantoko . (Jurnal Sain Veteriner, 2013)
Abstract Carp (Cyprinus carpio) is a freshwater fish with a high economic value, but very susceptible to diseases. One of effort to increase the productivity is by enhancing non-specific defense system. The purpose of this study is to determine the effect of carboxymethyl chitosan on enhancement non-specific defense system of carp. Carboxymethyl chitosan was obtained by alkylation process in which monochloroacetic acid in alkaline conditions was added. Carboxymethyl chitosan was given to carps at dosages of 30 μg/g, 75 μg/g and 105 μg/g, by intra muscular injection respectively. Seven and 14 days after administration of carboxymethyl chitosan, measurements of non-specific immune system parameters were done. The results showed that, administration of carboxymethyl chitosan on carps affected the phagocytic activity and lymphocytes counts. However, carboxymethyl chitosan did not give any effect to NBT activity, hematocrit, number of erythtocytes and leukocytes, monocytes and neutrophil counts in blood as well.